MORAL SEARCH IN MULTICULTURAL COMMUNICATION - I. A. Donnikova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of the work is to identify and justify the moral priorities in multicultural communication. Theoretical basis is the works of foreign and Ukrainian authors, revealing the main approaches to the problem of multiculturalism; studies on ethics and philosophical anthropology that define the problem field in the anthropo-logy of morality. The work uses: the conceptual provisions of phenomenology – for the disclosure of the semantic uncertainty of human existence as a prerequisite of moral search; existential philosophy – to substantiate the essential relationship of a man and culture. Originality of the results obtained consists of 1) understanding multiculturalism as a "dialogue of people" (V. Mezhuev), in which the moral search of every person is actualized; 2) in justifying the demand for inter-individual communication of "negative" ethics (A. Guseynov): its requirement not to commit immoral acts stimulates a person to moral search, reveals the specifics of the existence of a "person navigator" (S. Smirnov); 3) in the definition of intercultural communication as the creation of opportunities for the search for tolerant (non-conflict) forms of existence. Conclusions: 1) multiculturalism is a contradictory phenomenon, producing conflicts and creating prerequisites for overcoming them; 2) the possibilities of non-conflict existence in a situation of multiculturalism arise in inter-individual communication, which is a situation of moral search for every person; 3) "ethics of opportunities" unites universal and situational moral norms in multicultural communication: people enable each other to remain people; 4) "ethics of opportunities" creates conditions for tolerant (non-conflict) interaction between people and cultures.